Development of Djadoel Pekalongan Culinary Tourism Based on KHAS (Halal Culinary, Safe, and Healthy) - Muhammad Umar Andreanto; Jihan Mifta Sabila; Shinta Dewi Rismawati; Hendri Hermawan Adinugraha (Proceedings of Femfest International Conference on Economics, Management, and Business, 2024)
Pekalongan City is an area that has quite large potential to become a tourist attraction, one of which is the Djadoel Pekalongan Culinary Area. The Djadoel Pekalongan Culinary Area can be said to be quite unique culinary tourism because the area provides various types of traditional food and drinks. In line with the rise of the halal lifestyle trend, KNEKS issued guidelines for implementing the KHAS (Halal, Safe, Healthy Culinary) zone as a form of responding to the development of the Halal Lifestyle trend in Indonesia. Therefore, the application of the SPECIAL zone concept in the Djadoel Pekalongan Culinary Area has the potential to develop culinary tourism and become an attraction for tourists, especially Muslim tourists. This type of research is Qualitative Research. Data collection was carried out using field research and reference studies to find a KHAS-based method for developing the Djadoel Pekalongan Culinary Area. Based on the research conducted, a KHAS-based Djadoel Pekalongan Culinary Area development strategy has been prepared. In the process of developing the KHAS-based Djadoel Pekalongan Culinary Area, there are several aspects that need to be fulfilled, such as halal certification for the products produced. Apart from that, providing facilities such as clean water and places of worship is also one of the supporting aspects of implementing the KHAS zone in the Djadoel Pekalongan Culinary Area